DNA-PK Inhibitor, M3814, as a New Combination Partner of Mylotarg in the Treatment of Acute Myeloid Leukemia - Carr, Michael I.; Zimmermann, Astrid; Chiu, Li-Ya; Zenke, Frank T.; Blaukat, Andree; Vassilev, Lyubomir T. (Frontiers in Oncology, 2020)
Despite significant advances in the treatment of acute myeloid leukemia (AML) the long-term prognosis remains relatively poor and there is an urgent need for improved therapies with increased potency and tumor selectivity. Mylotarg is the first AML drug from a new generation of antibody drug conjugate (ADC) therapies aiming at the acute leukemia cell compartment with increased specificity. This agent targets leukemia cells for apoptosis with a cytotoxic payload, calicheamicin, carried by a CD33-specific antibody. Calicheamicin induces DNA double strand breaks (DSB) which, if left unrepaired, lead to cell cycle arrest and apoptosis in cancer cells. However, repair of DSB by the non-homologous end joining pathway driven by DNA-dependent protein kinase (DNA-PK) can reduce the efficacy of calicheamicin. M3814 is a novel, potent and selective inhibitor of DNA-PK. This compound effectively blocks DSB repair, strongly potentiates the antitumor activity of ionizing radiation and DSB-inducing chemotherapeutics and is currently under clinical investigation. Suppressing DSB repair with M3814 synergistically enhanced the apoptotic activity of calicheamicin in cultured AML cells. Combination of M3814 with Mylotarg in two AML xenograft models, MV4-11 and HL-60, demonstrated increased efficacy and significantly improved survival benefit without elevated body weight loss. Our results support a new application for pharmacological DNA-PK inhibitors as enhancers of Mylotarg and a potential new combination treatment option for AML patients.